2013
DOI: 10.1002/rcm.6698
|View full text |Cite
|
Sign up to set email alerts
|

On‐line triple oxygen isotope analysis of nitrous oxide using decomposition by microwave discharge

Abstract: A novel on-line analytical method was developed to measure the triple oxygen isotopes of N2O using microwave discharge to decompose N2O. This easy-to-use method is free from conditioning of reaction devices, and is applicable to molecules other than N2O such as NO and NO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…3 and they show that the carry-over was not statistically significant for any of the reaction units, as has also been reported before for quartz microwave. [13] When running alternating sets of CS and STD-N 2 O at different amounts (starting with the smallest amounts), the results of the smallest samples (10 nmol N 2 O) of STD-N 2 O indicate that a carry-over from the preceding CS samples (with highest amounts) might have occurred because these samples show a distinct deviation from the quantity dependence of the other samples (Fig. 4).…”
Section: Memory Effectsmentioning
confidence: 92%
See 4 more Smart Citations
“…3 and they show that the carry-over was not statistically significant for any of the reaction units, as has also been reported before for quartz microwave. [13] When running alternating sets of CS and STD-N 2 O at different amounts (starting with the smallest amounts), the results of the smallest samples (10 nmol N 2 O) of STD-N 2 O indicate that a carry-over from the preceding CS samples (with highest amounts) might have occurred because these samples show a distinct deviation from the quantity dependence of the other samples (Fig. 4).…”
Section: Memory Effectsmentioning
confidence: 92%
“…At higher N 2 O amounts, however, the precision is very good. Mukotaka et al [13] reported comparable precision for the microwave quartz, but no data on Δ 17 O was available for the gold wire oven. [12] CONCLUSIONS Taken together, the data indicate that two processes are affecting the quality of the Δ 17 O data: (i) exchange of sample oxygen with oxygen present in the reaction unit, and (ii) mass-independent fractionation when O 2 and N 2 are present in the ion source at the same time (although this mass-independent fractionation should also be possible in the reaction unit, as N 2 and O 2 are formed there simultaneously).…”
mentioning
confidence: 88%
See 3 more Smart Citations